2014
DOI: 10.1021/om5003123
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies on Platinum(II) Catalyzed Hydroarylation of Alkynes

Abstract: The dicationic acetylene platinum(II) complex [ P t ( P N P ) ( C 2 H 2 ) ] ( B F 4 ) 2 (PNP = 2,6-bis-(diphenylphosphinomethyl)pyridine) was generated in situ by ligand substitution from the ethylene complex [Pt(PNP)-(C 2 H 4 )](BF 4 ) 2 and was reacted with a series of arenes at low temperature. Only electron-rich arenes added across the coordinated C−C triple bond and gave the corresponding arylalkenyl complexes (E)-[Pt(PNP)(CHCHAr)]BF 4 (Ar = C 6 Me 5 , C 6 H 2 Me 3 -2,4,6, C 6 H 3 Me 2 -2,6, C 6 H 3 Me 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…Hahn et al reported that dicationic Pt(II) complexes activate alkynes once bound to the metal centre, to the point that they can undergo nucleophilic addition of electron-rich arenes under very mild reaction conditions through a Friedel-Crafts type process (as in Scheme 1). 31 Under acidic conditions it is possible to cleave the generated [Pt]-C bond releasing the hydroarylated product and regenerating the catalyst (Scheme 9). This last step is ratelimiting since it is known that protonolysis of dicationic [Pt]-C bonds is a rather difficult process.…”
Section: Hydroarylation Of C-c Multiple Bondsmentioning
confidence: 99%
“…Hahn et al reported that dicationic Pt(II) complexes activate alkynes once bound to the metal centre, to the point that they can undergo nucleophilic addition of electron-rich arenes under very mild reaction conditions through a Friedel-Crafts type process (as in Scheme 1). 31 Under acidic conditions it is possible to cleave the generated [Pt]-C bond releasing the hydroarylated product and regenerating the catalyst (Scheme 9). This last step is ratelimiting since it is known that protonolysis of dicationic [Pt]-C bonds is a rather difficult process.…”
Section: Hydroarylation Of C-c Multiple Bondsmentioning
confidence: 99%
“…Hydroarylation of alkynes provides a valuable route to various alkenes, although chemo-, regio and stereoselectivities of this reaction may be compromised by collateral formation of diaryl alkanes, dialkenyl arenes, and aryl dienes. An in situ generated dicationic complex [Pt(2,6-bis(dephinylphosphinomethyl)pyridine)C 2 H 2 ](BF 4 ) 2 151 reacts with arenes [ 184 ]. Only electron-rich arenes are incorporated into arylalkenyl products 152 ( Scheme 79 ).…”
Section: Acetylene In Organic Synthesismentioning
confidence: 99%
“…formation of alkynylpalladium complex 1218), followed by reductive elimination [1165]. Facile E/Z isomerization of alkenylplatinum complexes was attributed to resonance contribution from a carbene complex-carbocation form [1166]. A computational study of nickel-catalyzed [2+2+1] cycloaddition of a carborane and two silylalkyne units favored an alkyne insertion mechanism over a vinylidene mechanism [1167].…”
Section: )mentioning
confidence: 99%